2007
DOI: 10.1615/jenvironpatholtoxicoloncol.v26.i2.110
|View full text |Cite
|
Sign up to set email alerts
|

ALA and Malignant Glioma: Fluorescence-Guided Resection and Photodynamic Treatment

Abstract: Compared to normal cortex, mean PPIX fluorescence in vital tumor was found more than 100-fold increased. During PDT, the PPIX fluorescence bleached to 8%, 16%, and 1% of the initial intensity for the 100, 150, and 200 J/cm2 groups (median values). FGR: Contrast-enhancing tumor was completely resected in 65% of patients in the ALA group compared to 36% in the white-light group (p < 0.0001). Progression-free survival was superior in the ALA group compared to white-light patients with cumulative 6 months progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(99 citation statements)
references
References 0 publications
4
93
0
2
Order By: Relevance
“…without damaging the normal adjacent tissues, Stummer et al first attempted photodynamic diagnostic surgery using 5-aminolevulinic acid (5-ALA) in 1998 and demonstrated that normal brain tissue revealed no porphyrin fluorescence, whereas tumor tissue was distinguished by bright red fluorescence due to the response of glioma to 5-ALA. 28 Currently, fluorescence-guided resection is widely applied, 18,20,25,33 and it has certainly improved the resection rate and prognosis for gliomas. A randomized, controlled, Phase III trial demonstrated that the overall resection rate (65% vs 36%, respectively) and 6-month progression-free survival rate (41% vs 21%, respectively) were significantly improved in the 5-ALA assigned group compared with the control group.…”
mentioning
confidence: 99%
“…without damaging the normal adjacent tissues, Stummer et al first attempted photodynamic diagnostic surgery using 5-aminolevulinic acid (5-ALA) in 1998 and demonstrated that normal brain tissue revealed no porphyrin fluorescence, whereas tumor tissue was distinguished by bright red fluorescence due to the response of glioma to 5-ALA. 28 Currently, fluorescence-guided resection is widely applied, 18,20,25,33 and it has certainly improved the resection rate and prognosis for gliomas. A randomized, controlled, Phase III trial demonstrated that the overall resection rate (65% vs 36%, respectively) and 6-month progression-free survival rate (41% vs 21%, respectively) were significantly improved in the 5-ALA assigned group compared with the control group.…”
mentioning
confidence: 99%
“…In 2006 this same author reported a multicenter phase III trial comparing FIGS to placebo and found 64% complete surgical excision with fluorescence guided resection compared to 38% complete excision in the placebo group 27 . In 2007 Stepp and colleagues reported similar findings with GTR in 65% of patients undergoing FIGS compared to 36% in placebo group 28 . They also demonstrated improved 6 month progression free survival in 41% of patients in the study group vs 21% in the control group.…”
Section: Florescence Guided Resectionmentioning
confidence: 77%
“…The nonfluorescent PS precursor 5-aminolevulinic acid (5-ALA, trade name Levulan®) enhances the intrinsic production of protoporphyrin IX (PPIX) in mitochondria, which is activated by light illumination (~ 635 nm) following accumulation at the treatment site leading to the effective generation of reactive oxygen species within treated cells and triggering cell death [17,68,69]. The clinical use of topically applied 5-ALA for PDT was first introduced in 1990 [70] and followed by a wide range of clinical and preclinical studies for the PDT treatment of bladder cancer [71][72][73], chronic polyarthritis [74], malignant glioma [75], nonmelanoma skin cancers such as actinic keratosis (in combination with fluorescence dosimetry) [69,76], Barret's oesophagus and even multidrug resistant leukemia, the latter without much success [77]. In 2013 Bader et al reported a clinical trial using hexaminolevulinate (HAL), a 5-ALA derivative, for the PDT of bladder cancer in humans.…”
Section: Progress In Photosensitizer (Ps) Developmentmentioning
confidence: 99%